Retraction of the article: Mironov A.N., Sakaeva I.V., Dudchenko V.V., Korneeva L.V., Yavorsky A.N. International experience in drug names assessment: european medicines agency - article Editorial (Регуляторные исследования и экспертиза лекарственных средств)
.